Asconius on Cicero’s Son-in-law Lentulus, his Apprenticeship under Pupius Piso, and the De Othone - Ramsey, John T. (Ciceroniana On Line, 2021)
This paper covers three separate topics. All three concern Cicero and his first-century AD commentator Q. Asconius Pedianus. The chief contribution of parts one and two is to identify sources consulted by Asconius that have previously not been revealed or suspected. Part one will show that the multiple errors committed by Asconius in recounting the circumstances of the death of Cicero’s daughter Tullia in 45 BC are to be attributed to a source that misunderstood a letter of Cicero. Prior to publication, the letters to Atticus appear to have been accessible in a private archive, and on at least one, and probably two occasions, Asconius reveals that the historian Fenestella was misled by identifiable letters of Cicero to Atticus. Therefore, it is plausible that Fenestella was the conduit by which the content of yet another letter left its imprint on Asconius. In part two, it will be demonstrated that Asconius is likely to have relied upon, and been misled by, the invective against Cicero that has come down to us under the name of Sallust. This borrowing provides an earlier terminus post quem non for the circulation of that pseud-epigraphic work. At the same time, it demonstrates that Asconius, like Quintilian after him, almost certainly accepted the invective as a genuine work by Sallust. Lastly, part three challenges the communis opinio that a hostile reaction of a theatre crowd to the praetor L. Roscius Otho in 63 was caused by their resentment of his law of 67 which conferred on knights the privilege of occupying the first fourteen rows of seats. According to the prevailing view, Cicero’s no longer extant oration De Othone persuaded the throng to set aside their anger over being barred from the front rows. This paper argues that the angry outburst was triggered instead by the role Otho played as urban praetor in overseeing cases involving the repayment of debts, which in 63 had become a politically charged issue.